Fuzzy logic, deductive rules of inference and linguistic reasoning on knowledge base - Hồ, Nguyễn Cát (Journal of Computer Science and Cybernetics, 2016)
In this paper we introduce a notion of knowledge base consisting of statements with truth degree in which every statement may have several truth degrees. A set of rules of inference handling this kind of statements, a deductive reasoning method based on these rules will be considered. The consistency of the knowledge base will be also investigated.